Investigation of sperm cell antigens and crude sperm protein as potential immunocontraceptive agents in a rat model - Abubakar Abdulkarim (2023)
This study aimed at determining the effect of sperm cell antigens and crude sperm protein as potential immunocontraceptive agents in a rat model. A total of 36 Sprague Dawley rats consisting of 24 females and 12 males with ages ranging from 9 to 12 weeks were used in this study. The first experiment aimed to determine if SCA has an effect as an immunocontraceptive in rats. The rats were divided into three groups; Group A (control) rats were inoculated with 300ul of 9% normal saline, whilst, Group B and C rats were inoculated with 300ul of SCA solution B and C respectively. Breeding results revealed that female rats in group A delivered a total of 35 pups in comparison to the delivery of only 3 pups in Group B and 22 pups in group C. The delivery results showed that the litter sizes of the inoculated groups were significantly lower compared with normal births recorded in rats, P<0.001. This indicated that SCA was effective in reducing litter sizes, and the effects of infertility on the rats was influenced by the concentration of SCA inoculated. Histopathological examination of the uterus and the ovaries of the inoculated and control groups did not manifest evidence of pathological changes and the presence of corpus lutea in the ovaries indicated that all the female rats were actively cycling. The second experiment was aimed at determining, whether the use of CSP orally and subcutaneously would elicit similar immunocontraceptive effects. The breeding results revealed that female rats in group A delivered a total of 42 pups, group B a total of 23 pups and group C a total of 22 pups. The study hence, strongly suggested that CSP was effective in litter size reduction when used orally and subcutaneously. One Way ANOVA showed that the mean number of pups delivered in group A were significantly higher than the inoculated group B and C P<0.001. The histopathology slides showed the same result as the first experiment. The third experiment aimed to determine the expression level of genes related to fertility, follicle and embry development and implantation using quantitative real-time polymerase chain reaction (qRT-PCR). The results showed that all the fertility related genes (Wnt-2, Wnt-2b, and Fzd-4 in ovaries, and Wnt4, WntSa, and Wnt7a in uteri) were highly expressed. The gene expressed level for all the primers have a mean Ct value between 17 to 22, indicating a strong positive reaction of a high amount of target nucleic acid in the samples. In conclusion, the results of this study showed that, SCA and CSP have potential as immunocontraceptive agents, and qPCR implied that, the use of CSP does not affect the genes responsible for folliculogenesis, implantation, and embryogenesis.